2009
DOI: 10.1093/eurheartj/ehp313
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the index of microcirculatory resistance for invasively assessing myocardial viability immediately after primary angioplasty for anterior myocardial infarction

Abstract: Index of microcirculatory resistance, a new index representing microvascular integrity, is a reliable early on-site determinant of myocardial viability and LV recovery after primary stenting for AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 28 publications
7
67
1
Order By: Relevance
“…23 In the present study of STEMI patients, a higher mean IMR value than the optimal IMR cut-off value was recorded for the non-DP group, and a lower mean IMR value for the DP group. Although we did not confirm the significance of the secondary endpoints between the 2 groups, the lower IMR values in the DP group could possibly reflect remote recovery of left ventricular function.…”
Section: Distal Protection and Imr In Amicontrasting
confidence: 41%
See 2 more Smart Citations
“…23 In the present study of STEMI patients, a higher mean IMR value than the optimal IMR cut-off value was recorded for the non-DP group, and a lower mean IMR value for the DP group. Although we did not confirm the significance of the secondary endpoints between the 2 groups, the lower IMR values in the DP group could possibly reflect remote recovery of left ventricular function.…”
Section: Distal Protection and Imr In Amicontrasting
confidence: 41%
“…4, 24 Lim et al reported a mean IMR of 34 U in their patients with anterior AMI undergoing primary PCI with stenting. 23 The STEMI patients in the non-DP group of our study had a similar mean IMR value (37.2 U), whereas the DP group had a lower mean IMR value of 26.6 U, which clearly suggests that impaired coronary microcirculation among the patients with STEMI was reduced when DP was provided.…”
Section: Distal Protection and Imr In Amimentioning
confidence: 49%
See 1 more Smart Citation
“…5,6 In this case report, we presented the results from the comprehensive physiologic assessment in culprit vessel after primary PCI in STEMI patients and validated the results using cardiac MR findings. There is acute and overt inflammatory change in myocardial cell and vasculature, especially in acute phase of myocardial infarction.…”
Section: Casementioning
confidence: 77%
“…An IMR >32 U has also been associated with worse wall motion score on echocardiogram 3 months post STEMI. IMR after primary PCI has a strong inverse relationship with myocardial viability, as assessed by fluorine‐18 fluorodeoxyglucose positron emission tomography9 and predicts infarct size, left ventricular ejection fraction, myocardial salvage, and the presence and extent of microvascular obstruction and myocardial hemorrhage as determined by CMR 10. In a multicenter study involving 253 patients with STEMI treated with primary PCI and with a median follow‐up of 2.8 years, it was found that an IMR >31 was an independent predictor of death or rehospitalization, and an IMR >40 was an independent predictor of death.…”
Section: Introductionmentioning
confidence: 99%